DAYCARE CENTRE BANJARBARU - Raissa, Annaila; Wastuty, Prima Widia (UNIVERSITAS LAMBUNG MANGKURAT, 2025)
Child development during the golden period of growth aged 0-3 years, plays an important role in character formation, cognition and other important aspects. This phase requires good assistance, because it is the foundation for various aspects of a child's development. The four categories that influence a child's growth are gross motor skills, fine motor skills, language, and social/emotional. The city of Banjarbaru, with its rapid population growth, has a significant number of toddlers, but parents often have difficulty caring for children because many work outside the home. The daycare available in this city does not have adequate facilities, especially to help children's development based on their age. This is a problem raised in the design. The concept of “Interactive Design” is used to create an environment that stimulates children's development according to their age. The main room is divided into 4 child development age zones, each zone accommodates interactive elements for social adaptation, fine motor skills, gross motor skills and language. The tread design is adapted to the child's developmental needs in each zone for optimal stimulation.